Selection and the distribution of female real hourly wages in the United States - Iván Fernández-Val; Aico van Vuuren; Francis Vella; Franco Peracchi (Quantitative Economics, 2023)
We analyze the role of selection bias in generating changes in the observed distribution of female hourly wages in the United States using CPS data for the years 1975 to 2020. We account for selection bias from the employment decision by modeling the distribution of the number of working hours and estimating a nonseparable model of wages. We decompose changes in the wage distribution into composition, structural, and selection effects. Composition effects increased wages at all quantiles while the impact of the structural effects varied by time period and quantile. Changes in the role of selection only appeared at the lower quantiles of the wage distribution. The evidence suggests that there was positive selection in the 1970s, which diminished until the later 1990s. This reduced wages at lower quantiles and increased wage inequality. Post 2000 there appears to be an increase in positive sorting, which reduced the selection effects on wage inequality.
Keywords: C14; I24; J00; 330; Wage inequality; wage decompositions; selection bias